2016
DOI: 10.1093/eurheartj/ehw189
|View full text |Cite
|
Sign up to set email alerts
|

Subtype-specific promoter-driven action potential imaging for precise disease modelling and drug testing in hiPSC-derived cardiomyocytes

Abstract: Translational perspectiveCardiomyocytes (CMs) generated from human induced pluripotent stem cells are an evolving platform to understand molecular disease mechanism and evaluate cardiovascular drugs. A major limitation of this system is that they represent a heterogeneous mix of ventricular-, atrial-, and nodal-like CMs. By expressing a voltage-sensitive fluorescent protein under the control of lineage-specific promoters, we developed a convenient system allowing high-throughput subtype-specific optical action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
68
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 35 publications
5
68
0
Order By: Relevance
“…They then compared action potential characteristics and specific cardiac chamber markers using single cell PCR. While this does not constitute definitive proof, this study clearly showed that cardiac chamber-specific hiPSC-CM subtypes do exist (Chen et al 2016). However, given the varied action potential morphologies and characteristics, appropriate and robust methods to compare chamber-specific hiPSC-CM subtypes are required.…”
Section: Previous Differentiation Techniquesmentioning
confidence: 78%
See 2 more Smart Citations
“…They then compared action potential characteristics and specific cardiac chamber markers using single cell PCR. While this does not constitute definitive proof, this study clearly showed that cardiac chamber-specific hiPSC-CM subtypes do exist (Chen et al 2016). However, given the varied action potential morphologies and characteristics, appropriate and robust methods to compare chamber-specific hiPSC-CM subtypes are required.…”
Section: Previous Differentiation Techniquesmentioning
confidence: 78%
“…However, a very elegant recent study that combined electrophysiology, single cell RT-PCR, and optical action potential recordings showed that action potential characteristics are related to the expression of ventricular-, atrial-, and nodal-specific markers (Chen et al 2016). Chen et al…”
Section: Previous Differentiation Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…As these tools are genetically encoded, and equivalents have already been utilised in transgenic models [9,37], genome knock-in lines with constitutive and homogeneous expression may become useful adjuncts to this approach. Indeed, further refinement identifying particular cardiomyocyte subtypes by targeting promoters active in the atrium or ventricle, as demonstrated for lentiviral promoter:transgene combinations in SC-CMs [38] may be possible.…”
Section: Discussionmentioning
confidence: 99%
“…Applying minor modification to differentiation protocols such as adding neuregulin inhibitors [22] and retinoic acid regulators [23,24], and the usage of reporter gene constructs have proven successful in generating a relatively pure subtypes of cardiomyocytes including ventricular, atrial and nodal cardiomyocytes [25].…”
mentioning
confidence: 99%